Reinterpretation of the Islamic Education Thought of Burhan al-Islam al-Zarnuji: An Analysis of Islamic Epistemology - Afwadzi, Benny; Ali, Nur; Ahdi, M. Wafiyul (J-PAI: Jurnal Pendidikan Agama Islam, 2023)
The intellectual contribution of al-Zarnuji has significantly impacted the field of Islamic education. However, certain elements of society perceive his ideas as potential hindrances to contemporary progress. This article attempted to comprehensively reinterpret al-Zarnuji's beliefs through the lens of Islamic epistemology to promote constructive discourse between al-Zarnuji’s intellectual heritage and the dynamics of the modern era. It used a qualitative approach and a literature review method, with the book Ta’lim al-Muta’allim as the primary source. Through an examination of topics related to the diversity of knowledge and its legal dimensions, the intentions underlying the act of learning, and the reverence for knowledge and scholars, this article presents findings that elucidate al-Zarnuji's advocacy of two distinct epistemological paradigms: Bayani and Irfani. Among these paradigms, it is evident that Irfani's epistemology is more dominant than Bayani's. Irfani's reasoning significantly contributes to cultivating moral and spiritual aspects in learners. However, this thinking must not exert excessive hegemony over Islamic education. The most prudent course is maintaining a harmonious equilibrium among the three epistemologies–Bayani, Burhani, and Irfani–to ensure that Islamic education continues to progress.